2005
DOI: 10.1542/peds.2005-0682
|View full text |Cite
|
Sign up to set email alerts
|

Nonresponse Bias in a Follow-up Study of 19-Year-Old Adolescents Born as Preterm Infants

Abstract: ABSTRACT. Objective. To assess the effect of demographic and neonatal risk factors and outcome at the last available assessment on the probability of full responders, postal responders (those who only responded to the mailed questionnaire), or nonresponders in a follow-up study of 19-year-old adolescents who were born as preterm infants.Design. The 19-year follow-up program was part of a large ongoing collaborative study in the Netherlands on the long-term effect of prematurity and dysmaturity on various medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 17 publications
(14 reference statements)
9
70
1
Order By: Relevance
“…The scale ranges from 0 (no problems) to 2 perform a detailed drop-out analysis ruling out attrition bias concerning child health. The drop-out analysis is necessary in follow-up studies of VLBWI since the incidence of adverse outcomes have been shown to be underestimated when follow-up is incomplete, and boys, non-natives and those with low maternal education have participated less often [25,26]. In our study, parents of the boys responded more often than the parents of the girls.…”
Section: Discussionmentioning
confidence: 72%
“…The scale ranges from 0 (no problems) to 2 perform a detailed drop-out analysis ruling out attrition bias concerning child health. The drop-out analysis is necessary in follow-up studies of VLBWI since the incidence of adverse outcomes have been shown to be underestimated when follow-up is incomplete, and boys, non-natives and those with low maternal education have participated less often [25,26]. In our study, parents of the boys responded more often than the parents of the girls.…”
Section: Discussionmentioning
confidence: 72%
“…This pattern of loss to follow-up has been previously observed in longitudinal studies. 39 It is likely to have worked against our hypotheses as subject loss affects statistical power and children with social disadvantage are more likely to experience emotional problems. 40 Nevertheless potential bias cannot be excluded.…”
Section: Discussionmentioning
confidence: 97%
“…Those who participated across all time points were socially advantaged and had less risk of psychopathology (i.e., reduced prevalence), a pattern of selective dropout found in most longitudinal investigations (Hille et al 2005;Wolke et al 1995). This may work against stated hypotheses due to reduced statistical power, in particular, where disorders are infrequent such as depression in early adolescence.…”
Section: Discussionmentioning
confidence: 99%